Investigation of formation of well-known AGEs precursors in cookies using an in vitro simulated gastrointestinal digestive system - Yaman, Mustafa; Demirci, Mehmet; Ede-Cintesun, Elif; Kurt, Edanur; Faruk, Mızrak, Ömer; Yaman, Mustafa; Çintesun, Elif Ede; Demirci, Mehmet (Elsevier Ltd, 2022)
The present study investigated the influence of in vitro stimulated digestion system on the content of glyoxal and methylglyoxal in commercial cookies. Glyoxal and methylglyoxal levels in different cookie samples were analyzed before and after in vitro digestion with High Performance Liquid Chromatography. Initial glyoxal and methylglyoxal values ranged between 42.9 and 126.6 µg/100 g, and between 22.9 and 507.3 µg/100 g, respectively. After in vitro digestion, formation of glyoxal and methylglyoxal values were increased up to 645% and 698%, respectively. The results revealed that in vitro stimulated digestion conditions strongly increased the amount of glyoxal and methylglyoxal in cookies. The amount of fructose was found to be more effective on the formation of both GO and MGO than those of glucose and sucrose. Further studies are needed to extensively investigate glyoxal and methylglyoxal formation under in vitro conditions in such foods. © 2021 Elsevier Ltd
Keywords: Cookies; Formation; Glyoxal; In vitro; Methylglyoxal; High performance liquid chromatography; Condition; Cookie; Formation; Gastrointestinal; Glyoxal; High-performance liquid chromatography; In-vitro; In-vitro digestions; Methylglyoxal; Digestive system; advanced glycation end product; fructose; glucose; glyoxal; methylglyoxal; sucrose; apple; Article; cacao; chickpea; chocolate; controlled study; cookie; cream; digestion; food; gastrointestinal tract; ginger; high performance liquid chromatography; in vitro study; maize; nut; oat; orange (fruit); sesame; walnut; Chromatography, High Pressure Liquid; Food; Glucose; Glyoxal; Pyruvaldehyde